Only Connect: discovery pathways, library explorations and the information adventure - Helena Beeson (Association for Learning Development in Higher Education (ALDinHE), 2013)
Book review Walsh, A. and Coonan, E. (2013) Only Connect: discovery pathways, library explorations and the information adventure. Huddersfield: Innovative Libraries, pp.239, 978-099576652-1-7.